Propose a Framework for Competence of Organizing Experiential Activities for Student Teachers - Duong, Thị Kim Oanh; Nguyen, Văn Hiến (Journal of Technical Education Science, 2023)
In the educational content of the new general education program (2018), besides compulsory and elective subjects, there are also compulsory educational activities which are experiential activities (primary level) and experiential activities, career guidance (middle school and high school). In order to effectively implement this educational content, besides the training of traditional pedagogical competencies, which are teaching and educational competencies, student teachers need to be trained in a new competence named competence of organizing experiential activities. On the basis of analysis, comparison and generalization of relevant studies, the article proposes a framework for competence of organizing experiential activities for student teachers with three sub-competencies including competence of planning the organization experiential activities, competence of implementing the organization experiential activities and compentece of assessing the organization experiential activities. The proposed framework contributes to the improvement of pedagogical training programs in universities of education to meet the requirements of fundamental and comprehensive innovation in education and training. created under Resolution No. 29/NQ-TW (2013) at the 8th Conference of the Central Committee of the Communist Party of Vietnam (XI term).